Conditioning with busulfan plus melphalan versus melphalan alone before autologous haemopoietic cell transplantation for multiple myeloma: an open-label, randomised, phase 3 trial. Issue 5 (May 2019) - Bashir, Qaiser; Thall, Peter F; Milton, Denái R; Fox, Patricia S; Kawedia, Jitesh D; Kebriaei, Partow; Shah, Nina; Patel, Krina; Andersson, Borje S; Nieto, Yago L; Valdez, Ben C; Parmar, Simrit; et al.
Summary: Background: Retrospective studies suggest that conditioning therapy with busulfan plus melphalan could result in longer progression-free survival compared with melphalan alone in patients with multiple myeloma undergoing autologous haemopoietic cell transplantation (auto-HCT). We aimed to test this hypothesis in a randomised trial. Methods: The primary objective of the study was to compare progression-free survival with conditioning of busulfan plus melphalan with melphalan alone in patients with multiple myeloma. Patients with newly diagnosed multiple myeloma who were eligible for cell transplantation, aged 70 years or younger, with at least stable disease, were randomly assigned (1:1) to treatment. Patients received either busulfan plus melphalan, with a test dose of busulfan 32 mg/m 2 followed by pharmacokinetically adjusted doses on days −7, −6, −5, and −4 to achieve a target daily area under the curve (AUC) of 5000 mmol-minute and melphalan 70 mg/m 2 per day on days −2 and −1 (total melphalan dose 140 mg/m 2 ), or a melphalan dose of 200 mg/m 2 on day −2. Randomisation was performed via a Clinical Trial Conduct Website at the University of Texas MD Anderson Cancer Center. The accrual is complete and final results are presented here. The study is registered withClinicalTrials.gov, numberNCT01413178 . Findings: Between Oct 12, 2011, and March 22, 2017, 205 patients were assessed for eligibility and randomly assigned to treatment. The primary analysis of progression-free survival was measured in 202 patients who received treatment: 104 patients in the busulfan plus melphalan group and 98 patients in the melphalan alone group. 90 days after auto-HCT, 102 (98%) of 104 patients given busulfan plus melphalan and 95 (97%) of 98 patients given melphalan alone achieved partial response or better. The median follow-up in the busulfan plus melphalan group was 22·6 months (IQR 15·2–47·1) and 20·2 months (IQR 8·8–46·6) in the melphalan alone group. Median progression-free survival was 64·7 months (32·9–64·7) with busulfan plus melphalan versus 43·5 months (19·9–not estimated) with melphalan alone (hazard ratio 0·53 [95% CI 0·30–0·91]; p=0·022). There were no treatment-related deaths by day 100 in either group. Grade 2–3 mucositis was observed in 77 (74%) of 104 patients in the busulfan plus melphalan group versus 14 (14%) of 98 patients in the melphalan alone group. Interpretation: These findings, if confirmed in other ongoing studies, suggest that busulfan plus melphalan could replace melphalan alone as the conditioning regimen for auto-HCT in patients with newly diagnosed myeloma. Funding: This study was funded in part by the National Institutes of Health (NIH) throughMD Anderson's Cancer Center Support Grant (CA016672 ).